Risk communications: flood-prone communities of Kuala Lumpur - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza (Elsevier, 2013)
This paper discusses the contemporary academic debates in the field of social vulnerability, social capital and adaptation, and hazard management with a focus on sharing of knowledge on flood risk management between the flood-prone communities and the authorities in Kuala Lumpur, Malaysia. The study attempts to highlight the affected communities' vulnerability to environmental hazards, flood risk communication and management, all of which represent critical urban management issues in the rapidly expanding city of Kuala Lumpur. Respondents participating in this study include the various stakeholders consisting of several low-income squatter communities in Kuala Lumpur, officials from government agencies involved in flood risk management as well as community leaders. The study examines how the affected communities perceive their vulnerability and their responses in addressing these risks through their communications and sharing of knowledge among themselves, with the officials and other stakeholders.